Efforts to Control Blood Pressure among Hypertension Patients in the Community Health Center of Sei Mencirim Working Area, Medan, Indonesia - Agustina Boru Gultom; Arbani Batubara (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Community Health Center of Sei Mencirim working area had various health problems, one of which was hypertension. There were 2 villages have many cases of hypertension, including Sei Beras Sekata and Sei Mencirim Village. Lifestyle interventions can reduce blood pressure and other interventions such as pharmacology. Lifestyle interventions include dietary behavior, weight management, regular physical exercise and, stress management through progressive muscle relaxation exercises. Participants were 45 people with hypertension, divided into 2 groups consisting of 22 participants from Sei Beras Sekata and 23 participants from Sei Mencirim Village. The team has given educational intervention about efforts to control blood pressure and progressive muscle relaxation exercises by explaining, asking questions, giving examples, and inviting participants to do it. Measurement of knowledge used a questionnaire and, blood pressure used an Omron digital sphygmomanometer. Implementation activities included pre-test, intervention, and post-test were given on the same day. This activity was carried out in September 2020. The results of the intervention showed an increase in knowledge of 1.09, a decrease in systolic blood pressure of 9.42 mmHg and, a diastolic score of 4.64 mmHg. Education with progressive muscle relaxation exercises has increased knowledge scores, decreased systolic and diastolic blood pressure scores.